Esophageal adenocarcinoma in a first-degree relative increases risk for esophageal adenocarcinoma in patients with Barrett's esophagus. Issue 2 (March 2019) - Tofani, Christina J; Gandhi, Kunjal; Spataro, Joseph; Yoo, Joseph; Murphy, Megan; Mohan, Neena; Daitch, Zachary; Shah, Apeksha; Janowski, Raymond; Huntley, Colin; Dabbish, Nooreen; Keith, Scott; et al.
Background: The significance of a family history of esophageal adenocarcinoma in the progression to esophageal adenocarcinoma in patients with Barrett's esophagus has not been thoroughly evaluated. The purpose of this study is to evaluate the presence of esophageal adenocarcinoma in a first-degree relative in patients with Barrett's esophagus. Methods: A retrospective cohort study was conducted of patients with Barrett's esophagus at a tertiary care center undergoing radiofrequency ablation. Family history, demographics, and pathology and endoscopy reports were assessed in all patients. Findings: Three hundred and one patients with Barrett's esophagus were assessed. Nineteen patients who had a diagnosis of esophageal adenocarcinoma on index endoscopy were excluded. Nineteen (6.7%) patients had a first-degree relative with esophageal adenocarcinoma. Four (21.1%) of these patients progressed to esophageal adenocarcinoma. Of patients without first-degree relative with esophageal adenocarcinoma 22/263 (8.7%) progressed to esophageal adenocarcinoma. In a logistic regression model adjusted for sex and the number of radiofrequency ablation treatments, we found that family history of esophageal adenocarcinoma was a significant independent predictor of progression to esophageal adenocarcinoma (odds ratio = 5.55, 95% confidence interval: 1.47–20.0). Conclusion: Our study indicates that Barrett's esophagus patients with a first-degree family member with esophageal adenocarcinoma are at 5.5-fold higher risk for disease progression to esophageal adenocarcinoma. Family history of esophageal adenocarcinoma in Barrett's esophagus patients should be considered in patient surveillance and radiofrequency ablation treatment, beyond recommended guidelines.